2009
DOI: 10.1099/vir.0.016212-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunodominant epitopes in nsp2 of porcine reproductive and respiratory syndrome virus are dispensable for replication, but play an important role in modulation of the host immune response

Abstract: Non-structural protein 2 (nsp2) of porcine reproductive and respiratory syndrome virus (PRRSV) is the largest protein of this virus. In addition to its crucial role in virus replication, recent studies have indicated its involvement in modulating host immunity. In this study, each of the six identified immunodominant nsp2 B-cell epitopes (ES2-ES7) was deleted using a type I PRRSV cDNA infectious clone. Deletion of ES3, ES4 or ES7 allowed the generation of viable virus. In comparison with the parental virus, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
61
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 48 publications
2
61
0
Order By: Relevance
“…The highly conserved amino acids among OTU members are located at the putative Cys55-His124 catalytic motif of Nsp2. Moreover, it has been reported that immunodominant epitopes in Nsp2 play an important role in modulation of the host immune response (Chen et al, 2010b). In this study, we have provided evidence that PRRSV Nsp2 inhibits IFN induction by antagonizing the activation of IRF-3.…”
supporting
confidence: 56%
“…The highly conserved amino acids among OTU members are located at the putative Cys55-His124 catalytic motif of Nsp2. Moreover, it has been reported that immunodominant epitopes in Nsp2 play an important role in modulation of the host immune response (Chen et al, 2010b). In this study, we have provided evidence that PRRSV Nsp2 inhibits IFN induction by antagonizing the activation of IRF-3.…”
supporting
confidence: 56%
“…The observation that a complete HVR deletion mutant is replication competent in vitro but noninfectious in vivo suggests a less critical role for the HVR in cells with innate immunity defects. Nonstructural viral genes that are dispensable for virus replication are known to play a role in modulating host immune responses such as deubiquitinating and interferon antagonism activities (7,36). It will be interesting to determine if the HVR of HEV also contains critical residues that may play a role in antagonizing or evading host immune responses in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, one of the main targets used to monitor PRRSV evolution (25). Furthermore, the Nsp2-coding region is crucial for viral replication and modulation of host immunity because of its protease activity (2,8,13,42). Natural insertions and/or deletions are routinely observed in the hypervariable middle region of the Nsp2 protein in field strains, resulting in polymorphisms of considerable size (16,31).…”
Section: Discussionmentioning
confidence: 99%